Step by Step for Social Innovation with Neuro-Fuzzy Modelling - Somosi, Mariann Veresné; Varga, Krisztina; Kocziszky, György (European Journal of Economics and Business Studies, 2019)
Innovation as the key element of economic development is a crucial factor in social processes. Technical innovations can be identified as prerequisites and causes of social change and cannot be created without the renewal of society. Technological and economic innovations cannot respond to all social challenges. Natural and material resources are becoming more and more scarce, so it is necessary to use investment assets as efficiently as possible, maximizing social and economic efficiency. It is a major task to address the backwardness of social disparities and to create opportunities for catching up in peripheral regions.The aim of our study is to identify the local level of catching-up opportunities that arise from social innovation efforts, and model values for other disadvantaged areas. The investigated solution is presented as a case study after a structured analysis of the local initiatives of the settlement. In addition to examining the prominent role of local actors and networks, we present the process of social innovation, the framework conditions that determine systemic functioning, as well as the social needs, potentials and barriers that determine social innovation efforts.The study identifies the social, economic and political challenges associated with social needs in peripheral regions, as well as proposals for solutions based on neuro-fuzzy modelling that can be adapted to other disadvantaged areas. Exploring solutions and innovative structures and collaborations provides an opportunity to demonstrate the role of the social innovation process in local-level catching-up initiatives.
Keywords: social innovation, disadvantaged settlements, catching up, neuro-fuzzy modelling, process orientation